SCIENCE LITERACY INDICATORS IN OPTICAL INSTRUMENTS OF HIGHSCHOOL PHYSICS TEXTBOOKS CHAPTER (Department of Physics, Faculty of Mathematics and Natural Sciences, 2017)
The direction of current science is emphasized on the importance of science literacy skill as a preparation for students returning to community after finishing school. Science literacy skill is believed can help the individuals to solve the problem scientifically and accountable. Science textbooks are instructional tools that help students learning science. The purpose of this research is to analyse the textbooks of Physics for high school grade X about Optical Instruments topic based on science literacy indicator. The study conducted in four senior highschools. There were two textbooks used in those schools, Book A and Book B. The results showed that on average the emergence of science literacy indicator of science nomenclature was 17.5%, intellectual process skills was 45.5%, the rules of scientific evidence was 8.5%, postulate of science was 19%, and scientific disposition was 9.5%. Book A contained of more research activities than Book B, but Book B linked the second indicator more comprehensive. The advantages and disadvantages of each analyzed textbooks can be used as a further background study for developing the good quality teaching material of physics-based scientific literacy.